2020
DOI: 10.1097/gox.0000000000003032
|View full text |Cite
|
Sign up to set email alerts
|

Average Models and 3-dimensional Growth Patterns of the Healthy Infant Cranium

Abstract: Background: Treatment of cranial deformity is often performed during infancy in cases such as craniosynostosis and deformational plagiocephaly. To acquire morphologic standards for the treatment goals of these conditions, we created cranial average models and elucidated the growth patterns of the cranium of healthy infants in 3-dimension (3D) using homologous modeling. Methods: Homologous modeling is a technique that enables mathematical analysis of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Recently, 3D growth pattern of the cranium of healthy Japanese infants was reported. 20) They divided the period up to 17 months of age into six age groups and analyzed which parts of the cranium grew during the two adjacent age groups. They reported that up to 5 months of age, the entire area of cranium, except for the occipital region, undergoes rapid growth.…”
Section: Icv Two-dimensional Parameters and CI Datamentioning
confidence: 99%
“…Recently, 3D growth pattern of the cranium of healthy Japanese infants was reported. 20) They divided the period up to 17 months of age into six age groups and analyzed which parts of the cranium grew during the two adjacent age groups. They reported that up to 5 months of age, the entire area of cranium, except for the occipital region, undergoes rapid growth.…”
Section: Icv Two-dimensional Parameters and CI Datamentioning
confidence: 99%
“…10 This is likely contributed by the different measurement methods, as shown in this review, in addition to the inherent difficulty in locating standard anatomic landmarks, a common methodological step in many of the studies. 10-18…”
Section: Discussionmentioning
confidence: 99%
“…A unique methodology employed by Kuwahara et al 11,12 provides average models of healthy Japanese infants that were constructed via homologous modeling. Homologous modeling enabled the group to identify 7 principal components as to which part of the cranial shape each component was related to, allowing for easy characterization of cranial morphology noted in some clinical conditions that alter cranial morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First proposed by Blanz and Vetter ( Blanz and Vetter, 1999 ; Booth et al, 2016 ) in 1999, 3DMMs have proven adept at modelling complex shape structures such as the human face, head, hand and ear ( Blanz and Vetter, 1999 ; Booth et al, 2016 ; Dai et al, 2018 ; Ploumpis et al, 2019 ; Dai et al, 2017 ; Zolfaghari et al, 2016 ; Khamis et al, 2015 ) despite limited input data. Paediatric skull models have also been constructed using 3DMMs, although the ability of these models to generate synthetic data has not yet been tested ( Li et al, 2015 ; Kuwahara et al, 2020 ; Libby et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%